Electrochemically synthesized sulfur-doped graphene as a superior metal-free cathodic catalyst for oxygen reduction reaction in microbial fuel cells. Issue 105 (31st October 2016) - Han, Thi Hiep; Parveen, Nazish; Ansari, Sajid Ali; Shim, Jun Ho; Nguyen, Anh Thi Nguyet; Cho, Moo Hwan
Abstract : Electrochemically synthesized S-GN was proved to be an efficient alternative cathode catalyst to Pt/C in microbial fuel cell. Abstract : Platinum nanoparticles (PtNPs) have long been regarded as the benchmark catalyst for the oxygen reduction reaction (ORR) in the cathode of microbial fuel cells (MFCs). On the other hand, the practical applications of these catalysts are limited by the high cost and scarcity of Pt. Therefore, developing an alternative catalyst to PtNPs for efficient ORR activity is essential for meeting the future demands for practical applications in MFCs. In this study, sulfur-doped graphene (S-GN) was synthesized via the environmental friendly, economical and facile one pot electrochemical exfoliation of graphene in a unique combination of electrolytes, which both catalyzed the exfoliation reaction and acted a sulfur source. The initial activity of S-GN as an ORR active catalyst was examined by cyclic voltammetry (CV), which showed that the as-synthesized S-GN exhibited better ORR activity than the plain material. Furthermore, the application of S-GN as a cathode material was also studied in MFCs. The results showed that the MFC equipped with the S-GN cathode produced a maximum power density of 51.22 ± 6.01 mW m −2, which is 1.92 ± 0.34 times higher than that of Pt/C. The excellent performance of S-GN as a cathode catalyst in MFCs could be due to the doping of graphene with heteroatoms, which increased the surface area and improved the conductivity of graphene through a range of interactions. Based on the above MFC performance, the as-synthesized S-GN catalyst could help reduce the cost and scale up the design of MFCs for practical applications in the near future.